Form two students' ideas of solving algebraic expressions :a case study at secondary school in Sarikei district - Wong, Huang Yew (Universiti Malaysia Sarawak, UNIMAS, 2009)
This research is carried out to investigate Form Two students’ ideas of solving Algebraic Expressions. Algebraic Expressions is defined as Mathematics objects with one or more variables together with other components such as number and signs. Algebraic Expressions is second topic in Form Two Mathematics syllabus and every student has to learn the topic. This research is to investigate what are the students’ ideas in solving the questions about Algebraic Expressions. Data collection involves three types of data collected, they are think aloud data where students talk aloud what they think while solving the questions given, written documents and interviews data. Six questions from topic Algebraic Expressions are chosen and used to investigate Form Two students’ ideas of solving Algebraic Expressions. The analysis of the collected data indicated that there were common ideas used by the students. The ideas are categorized into ideas that are relevant and not relevant to standard Mathematics views. The findings generate thirty two models of Form Two students’ ideas of solving Algebraic Expressions. This research benefits teachers, students and Mathematics education.